Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN): an update - O. Mogole; N. Schellack; M. H. Motswaledi (South African Family Practice)
Stevens-Johnson syndrome (SJS) is a form of toxic epidermal necrolysis (TEN) a rare but life-threatening hypersensitivity reactions that affect the skin and mucous membranes. The most common triggers are drugs, but they can also be triggered by infections. Granulysin has been recently identified as the major molecule responsible for the widespread keratinocyte necrosis. Early identification and removal of causative agent is crucial in preventing progression of condition and reducing patient mortality. Supportive care is often recommended over immunomodulating treatments as it helps improve patient outcome.